2020
DOI: 10.1149/2162-8777/abbea0
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of 5-Methyl-1H-Benzotriazole and Sodium Dodecyl Benzene Sulfonate on CMP Performance of Ruthenium Barrier Layer in KIO4-Based Slurry

Abstract: The chemical mechanical polishing (CMP) of ruthenium barrier layer of copper interconnection for 14 nm and below technology node has been connected with more challenges, among which the corrosion of copper and ruthenium and the selectivity of removal rate between ruthenium and copper has attracted more attention. This paper mainly focus on the influence of 5-methyl-1H-benzotriazole(MBTA) and sodium dodecyl benzene sulfonate (SDBS) on the polishing properties of copper and ruthenium during ruthenium barrier CMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Compared with slurry A, the addition of EDA in slurry B improves the removal rate of ruthenium, but the removal rate of copper is remarkably higher than that of ruthenium. On this basis, the corrosion inhibitor combination for copper in another study 50 is added (as shown in slurry C), and successfully adjust the removal rate selectivity to 1.13 : 1.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with slurry A, the addition of EDA in slurry B improves the removal rate of ruthenium, but the removal rate of copper is remarkably higher than that of ruthenium. On this basis, the corrosion inhibitor combination for copper in another study 50 is added (as shown in slurry C), and successfully adjust the removal rate selectivity to 1.13 : 1.…”
Section: Resultsmentioning
confidence: 99%
“…There is a stable current between a certain range of potentials, which proves that the corrosion inhibition effect of copper is related to the formation of a protective film. 17,18,[20][21][22][23] The main cathodic reactions were the reactions of oxygen reduction as follows: 23…”
Section: Resultsmentioning
confidence: 99%
“…2, has received a lot of attention as an azole inhibitor. At the same concentration, the inhibition performance of TTA is better than benzotriazole (BTA), and it is easier to be removed in the post-cleaning [21,22]. Yin et al [23] studied the suppressive mechanism of BTA and TTA on the Cu surface by quantum chemical method.…”
Section: Introductionmentioning
confidence: 99%